Fabrication of fanlike L-shaped graphene nanostructures with enhanced thermal/electrochemical properties via laser irradiation. (September 2021) - Park, Seungyoung; Ji, Seulgi; Yoon, Yeoheung; Kim, Seong Ku; Song, Wooseok; Myung, Sung; Lim, Jongsun; Jung, Ha-Kyun; Lee, Sun Sook; An, Ki-Seok
Abstract: Engineering can be used to create uniquely oriented 2D materials, especially graphene, and can play a crucial role in the development of multifunctional films for applications in supercapacitors and thermal management, imparting excellent electrical and thermal properties to the films. However, the preparation of a uniquely structured graphene film with high-quality often requires a complex multi-step technique. Herein, we propose a facile and efficient one-step laser irradiation process for the synthesis of multifunctional laser-induced graphene electrodes consisting of L-shaped reduced graphene oxide nanosheets with vertical alignment (VrGO). Notably, the instantaneous high thermal energy of the laser irradiation can heal the defects of graphene oxide (GO) nanosheets, thus, enhancing the electrical conductivity and crystallinity while inducing the vertical alignment. Additionally, the vertical alignment of high-quality GO nanosheets leads to more isotropic thermal transport, thus, enhancing the out-of-plane thermal conductivity to 6.202 W m −1 K −1 . GO nanosheets also exhibited superior performances as supercapacitor electrodes, demonstrating an outstanding areal capacitance of 36.8 mF cm −2  at 1.2 mA cm −2, and excellent stability up to 10, 000 cycles of charging/discharging. This simple laser technique opens up new possibilities for engineering the structural and physical properties of graphene for applications in various fields that require functional thin films. Graphical abstract: Image 1 Highlights: The rapid reduction of graphen oxide (GO) by CO2 -laser is performed. Defect-healing and vertical alignment of GO nanosheets were achieved. Enhancement of out-of-plane thermal conductivity with the vertical alignment. Defect-less, vertical graphene sheets exhibit excellent supercapacitor performance.